Cerita Lisan Lukisan Bunuh Diri Raden Saleh Sebagai Inspirasi Penciptaan Tari Rundung Saleh - Ida Bagus Ketut Sudiasa; Tuteng Suwandi; Hendrik, Putri Annisa (Jurnal Pendidikan Tari, 2022)
Bullying is a situation where a person or a group of people abuse their power. Saleh is taken from the name of the inspirational figure, Raden Saleh Syarif Bustaman. Rundung Saleh depicts a story of bullying experienced by Raden Saleh Syarif Bustaman. The correlation of the title and the story of bullying experienced by Raden Saleh is that bullying still happening nowadays. The "Rundung Saleh" dance work is based on the basic movements of the keurseus dance and daily movements using the Alma M Hawkins creation method. The process and results of the embodiment of the dance work is presented in dance film format, which is the result of movement variations through a cinematic process and animated by natural elements or technological manipulation. Therefore, this dance work "Rundung Saleh" is using a shooting techniques according to the concept of stage arrangement or decorative room. The presentation of the dance work uses a dramatic dance type and a double cone dramatic design with a symbolic representational presentation mode.